A Facile and Efficient One-Pot Procedure for the Synthesis of Novel 2-Substituted 3-Thioxoisoindolin-1-one Derivatives - Gholami, Fatemeh; Moazzam, Ali; Bahadorikhalili, Saeed; Adib, Mehdi; Hosseini, Samanesadat; Larijani, Bagher; Mahdavi, Mohammad (Synlett, 2022)
In this paper, a novel and efficient method is reported for the synthesis of novel 2-substituted 3-thioxoisoindolin-1-one derivatives. The method is based on the solvent-free reaction of 2-carboxybenzaldehyde with aliphatic amines and sulfur at 100 °C. This reaction is intensely significant, especially in pharmacy applications, due to the facile synthesis of asymmetric thioxoisoindolin-1-one derivatives with phthalimide backbones.
Keywords: 3-thioxoisoindolin-1-one; sulfur containing compound; phthalimide; multicomponent reactions